(untitled) (Journal of Guidance and Counselling Studies, 2021)
This study investigated the effects of problem-solving technique on test anxiety and academic performance of secondary school students. The study adopted a quasi- experimental pre-test post-test research method. Three null hypotheses were generated and tested at 0.05 level of significance. Sixty nine students identified with high anxiety level were selected for the study. The selected samples were grouped into experimental and control groups. A Test Anxiety Scale developed by the researchers and validated was used for the study. The questionnaire was administered to identify students’ level of test anxiety before and after the treatment. The experimental group was taken through six weeks of problem-solving technique. Data collected were analyzed using analysis of covariance (ANCOVA). The results revealed there was significant difference in the test anxiety levels between the two groups in the post test. Also there was improvement in the academic performance of students in the experimental group who received the problem solving technique. Based on these findings, it was concluded that problem-solving technique is effective in reducing test anxiety levels among students.